Multilayer film having foamed polyolefin-based adhesive composition
Patent Information
- Application Number
- JP2023554281
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-03-12
- Filing Date
- 2022-03-10
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-03-10
AI Technical Summary
Existing multilayer film structures face challenges in achieving improved toughness and optical properties without adding thickness or using expensive polymers, particularly in bonding layers of polyethylene, propylene, styrene, and polar polymers like EVOH or nylon, where conventional tie layers fail to provide adequate adhesion and clarity.
A foamed polyolefin adhesive composition is used as a tie layer, formed by dissolving gas in a polyolefin adhesive within an extruder, which is then discharged through a die to create a matrix with dispersed gas cells. The cooling process is controlled to collapse these cells before solidification, enhancing adhesion and optical properties.
The foamed tie layer improves toughness and clarity in multilayer films, demonstrated by increased dart drop impact resistance and reduced haze, while maintaining or improving mechanical properties without adding thickness or using expensive materials.
Abstract
Description
[Technical field]
[0001] This application claims priority to U.S. Provisional Application No. 63 / 053,425, filed under the Patent Cooperation Treaty, and filed July 17, 2020, the entire contents of which are incorporated herein by reference.
[0002] The present invention relates to a multilayer film structure that includes a foamable adhesive composition as a tie layer between two other layers. The multilayer film that includes a foamed adhesive tie layer exhibits improved toughness and optical properties compared to multilayer film structures with conventional tie layers. The present invention also relates to a method for making a multilayer film structure that includes a tie layer that includes the foamed adhesive composition. [Background technology]
[0003] Tie layer adhesives are used to bond polyolefins to dissimilar substrates in multi-layer coextrusion structures, especially for blown and cast film, extrusion coating, blown, sheet extrusion, wire and cable, pipe, and other industrial applications. In particular, the adhesives are useful for bonding plastics, wood, glass, paper, composites, metal substrates, and incompatible polymers. Tie layer adhesives can be used in lamination, coextrusion, extrusion coating, and other processes.
[0004] Tie layer adhesives generally consist of and / or contain polyolefin-based resins and grafted polyolefins, which may or may not be predominant. Grafted polyolefins are made by reacting polyolefins with unsaturated monomers at elevated temperatures with or without the presence of a radical initiator. Commercially available tie layer adhesives include Plexar™ resins, products available from LyondellBasell that contain anhydride modified polyolefins.
[0005] Multilayer films and sheets are widely used in food packaging applications and bulk material packaging. The number and arrangement of resin layers and the type of resin used vary depending on the application. Polyethylene resin is often used as one of the layers for food contact and sealing properties. Ethylene-vinyl alcohol (EVOH) copolymers and polyamides (nylons) are commonly used as oxygen barrier layers. It would be desirable to improve the toughness and clarity of multilayer film structures with improved tie layers without adding thickness or using more expensive polymers to the existing performance layers of the structure. However, it has always been difficult to bond different resin layers in multilayer films and sheets.
[0006] There is a need for improved tie layer adhesive compositions suitable for use in producing multi-layer constructions with good adhesion, high clarity and improved toughness. A valuable approach would avoid performance trade-offs with expensive additives. Ideally, the improved tie layer adhesives could be produced using economical starting materials, commonly used equipment, and familiar techniques.
[0007] Polyolefin-based adhesive compositions formed by melt blending an olefin-based polymer with a functionalized polyolefin and the use of the adhesive composition as a tie layer in a multi-layer construction are disclosed in U.S. Patent Publication No. 2017 / 0335149. Adhesives comprising linear low density polyethylene grafted with maleic anhydride and the use of such adhesives as tie layers in multi-layer constructions are disclosed in U.S. Patent No. 10,053,574.
[0008] However, multi-layer constructions including layers of polyethylene, propylene polymers, styrene polymers, and / or polar polymers (e.g., EVOH or nylon) still need to have a common tie layer that can bond the different layers in the structure while maintaining or improving mechanical and / or optical properties. Summary of the Invention
[0009] In general, the present disclosure relates to a multi-layer construction comprising a base layer, an outer layer, and a tie layer disposed between the base layer and the outer layer. The tie layer comprises a foamed polyolefin-based adhesive composition. The polyolefin-based adhesive composition, as defined herein, is foamed by applying the following steps:
[0010] In some embodiments, the polyolefin adhesive composition and a gas soluble in the polyolefin adhesive composition are added to an extruder. The polyolefin adhesive composition and the gas are mixed in the extruder under conditions of pressure and temperature sufficient to form a mixture of the molten polyolefin adhesive composition and the dissolved gas. The mixture of the molten polyolefin adhesive composition and the dissolved gas is then discharged from the extruder through a die attached to the extruder. The pressure of the mixture is reduced by the discharge of the material from the die in an amount sufficient to produce a matrix of the molten polyolefin adhesive composition containing a dispersed phase of gas cells or bubbles.
[0011] The molten polyolefin adhesive composition containing dissolved gas is discharged simultaneously with or immediately before the discharge of the molten material forming the base layer and the outer layer from the die fed by another extruder. Optionally, one of the two outer layers may be a non-polymeric substrate rather than a polymer. The die discharge is arranged to co-extrude the layers from the multiple dies to form a multilayer film, with the tie layer between the base layer and the outer layer and bonded to each other in the same area. The cooling rate of the multilayer extrudate is controlled to induce a higher enthalpy state in the tie layer matrix, which causes at least some of the gas cells or bubbles in the tie layer to collapse before the matrix solidifies. The cooling of the extrudate can be controlled to collapse the bubbles. This controlled cooling allows internal stresses to be relieved, as indicated by the higher final enthalpy state of the tie layer matrix.
[0012] In some embodiments, the addition of gas to the extruder is accomplished by pyrolysis of a chemical blowing agent. In other embodiments, a physical blowing agent is used and the gas is injected into the extruder from an external source. Chemical and physical blowing agents can be used alone or in combination with a nucleating agent to promote a more uniform bubble distribution.
[0013] One or more embodiments include a multilayer film including a second outer layer and a second tie layer disposed between the second outer layer and the base layer, the second tie layer including the foamed polyolefin-based adhesive composition. Other embodiments include various combinations of additional layers, some having only an additional outer layer and some having an additional outer layer and a tie layer. The tie layer is most valuable as a connection between two other layers that are not similar or compatible with each other.
[0014] The present disclosure also provides a process for forming a multi-layered construction. The polymeric compositions forming each layer of the multi-layered construction are prepared by heating and mixing the polymeric compositions in a molten state, such as by an extruder. The polymeric compositions of each layer may be a single polymer or a blend of different polymers, and in either case may optionally include one or more additives. The extrusion barrel and screw not only promote a uniform and consistent temperature of the polymer melt during preparation, but also ensure thorough mixing of the individual components and / or additives.
[0015] In the extruder, the polymeric composition of the tie layer comprises a polyolefin adhesive composition containing dissolved gas. In some embodiments, the dissolved gas is formed by adding a chemical blowing agent to the polyolefin adhesive composition. The pressure and temperature conditions maintained in the extruder are sufficient to cause thermal decomposition of the chemical blowing agent and are maintained sufficient to keep the gas resulting from this thermal decomposition dissolved in the molten polyolefin adhesive composition. In other embodiments, the dissolved gas is formed by adding a gas directly to the molten polyolefin adhesive composition, for example by injecting it into the extruder barrel from a separate source. The pressure and temperature conditions maintained in the extruder are sufficient to promote mixing and distribution of the added gas throughout the molten polyolefin adhesive composition and to keep the gas dissolved in the molten polyolefin adhesive composition.
[0016] The polymer compositions forming each layer of the multilayer film are co-extruded to form a multi-layer melt of the polymer compositions including at least a base layer, a first outer layer, and a tie layer disposed between and co-adhered to the base layer and the first outer layer. During co-extrusion, for the tie layer, the polymer composition of the tie layer is foamed by applying a pressure to the molten polyolefin adhesive composition containing dissolved gas as the tie layer polymer composition exits the extruder through a die. This foaming occurs when the dissolved gas in the molten polyolefin adhesive composition comes out of solution and forms a dispersed phase of gas cells in the molten polymer matrix.
[0017] The multilayer melt formed after coextrusion is cooled at a controlled rate to induce at least a partial collapse of the gas cells in the bonded layers and solidify. In some embodiments, the cooling rate is controlled to allow most or substantially all of the gas cells to collapse. The desired amount of gas cell collapse, and therefore the desired cooling rate, can be determined by observing the opacity or transparency of the multilayer melt and / or the final multilayer film prior to solidification.
[0018] The foregoing has outlined rather broadly the features and technical advantages of the present invention in order that the detailed description of the invention that follows may be better understood. Additional features and advantages of the invention will be described below which form the subject of the claims of the invention. It should be appreciated by those skilled in the art that the conception and specific embodiments disclosed may be readily utilized as a basis for modifying or designing other membrane structures and / or processes for carrying out the same purposes of the present invention. Those skilled in the art will also realize that such equivalent structures do not depart from the spirit and scope of the invention as set forth in the appended claims. The novel features of the present invention, including its structure and method of manufacture, as well as other objects and advantages, will be better understood from the following description. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] Exemplary embodiments of the claimed subject matter below will now be disclosed. For purposes of clarity, some features of an actual implementation may not be described herein. It should be understood that in developing such an actual embodiment, many implementation-specific decisions must be made to achieve the developer's particular goals, including complying with system-related and business-related constraints that vary from implementation to implementation. Moreover, it should be understood that such development efforts, even if complex and time-consuming, would be routine for those of ordinary skill in the art having the benefit of this disclosure.
[0020] The words and phrases used herein should be understood and interpreted as having a meaning consistent with the understanding of those words and phrases by those of ordinary skill in the art. A special definition of a term or phrase, i.e., a definition that is different from the common and customary meaning as understood by those of ordinary skill in the art, is not intended to be implied by the consistent use of the term or phrase herein. To the extent that a term or phrase is intended to have a special meaning, i.e., a meaning other than the broadest meaning as understood by those of ordinary skill in the art, such a special or specific definition will be expressly described in the definitions section of the specification to provide a special or specific definition of the term or phrase.
[0021] For example, the following description includes a non-exhaustive list of definitions of some specific terms used in this disclosure (other terms may be defined or clarified elsewhere herein). These definitions are intended to clarify the meaning of the terms used herein. It is believed that these terms are used in a manner consistent with their ordinary meaning, yet the definitions are provided here for clarity. definition
[0022] As used herein, "barrier layer" refers to a layer used in multilayer films that imparts gas impermeability to the multilayer construction in addition to other desired properties.
[0023] As used herein, "multilayer film" means a coextruded structure that includes at least a barrier layer, a structural layer, and a tie layer.
[0024] As used herein, "non-polar comonomer" refers to a monomer unit that contains only carbon and hydrogen.
[0025] As used herein, "non-polar polymer" means a polymer or copolymer composed of units derived from non-polar monomers.
[0026] As used herein, "polar monomer" means a monomer that contains a highly electronegative atom, such as chlorine, fluorine, oxygen, nitrogen, or sulfur, that results in a polymer that contains a permanent electric dipole.
[0027] As used herein, "polar polymer" means a polymer or copolymer that includes units derived from polar monomers.
[0028] As used herein, "polyolefin-based adhesive composition" means any composition comprising a functionalized polymer, alone or in combination with other polymers, where one layer of the polyolefin-based adhesive composition (or "tie layer") adheres better to a first and a second polymer layer, in the case of polymer coextrusion layers, than the first and second polymer layers adhere to each other. Examples of polyolefin-based adhesive compositions are disclosed in U.S. Patent Publication Nos. 2017 / 0198103 and 2017 / 0335149, as well as U.S. Patent Publication Nos. 7,687,575, 7,871,709, 8,598,264, 8,673,451, 8,685,539, 9,499,723, 9,650,548, 9,662,864, 9,676,971, 9,803,074, 10,053,574, 10,150,894, 10,240,072, and 10,266,727, the contents of which are all incorporated herein by reference in their entirety. As noted above, the tie layer can also improve adhesion when one or both polymeric layers are replaced with a non-polymeric layer.
[0029] As used herein, "structural layer" means a layer used in a multilayer film to impart desired mechanical properties and / or moisture resistance to the multilayer construction. Multilayer Film
[0030] Large bulk packaging for fresh goods such as meat and cheese wraps, snack foods, baking mixes, and dog food requires multi-layer construction to prevent oxygen and moisture transmission. EVOH and nylon are particularly well suited for packaging food, medicines, cosmetics, and other perishable or delicate items because they have high transparency, excellent flex crack resistance, and some of the best barrier properties against gases such as oxygen, nitrogen, and carbon dioxide, which can extend the shelf life. Compared to many other common films, polar polymers such as EVOH and nylon have excellent barrier properties. However, the excellent gas barrier properties of many polar polymers such as EVOH and nylon are degraded when exposed to moisture.
[0031] Non-polar polymers such as polyethylene and polypropylene have excellent moisture resistance. Therefore, to optimize both cost and performance, polar and non-polar polymer layers such as HDPE, PP, and PET are often combined in multi-layer coextruded films because of their excellent moisture resistance. However, polar and non-polar polymers cannot adhere well to each other, so an adhesive composition must be used as a bonding layer between different polymer layers.
[0032] The adhesive composition suitable for use as the bonding layer of the multi-layer construction has good adhesion to both polar and non-polar polymers. Examples of polar polymers include, but are not limited to, acrylonitrile butadiene styrene, ethylene vinyl acetate, EVOH, ethylene n-butyl acetate, ethylene methyl acrylate copolymer, ethylene acrylic acid copolymer, nylon, polycarbonate, and polymethyl methacrylate. Examples of non-polar polymers generally include, but are not limited to, polyethylene homopolymer, ethylene-α-olefin copolymer, polypropylene homopolymer, propylene-α-olefin copolymer, and polyolefin.
[0033] In some embodiments, the multi-layer construction comprises: (A) a first polyolefin layer; (B) a first polar polymer layer; (C) at least one tie layer between the polyolefin layer and the polar polymer layer.
[0034] A common process for forming a multi-layer construction includes co-extruding layers to form the multi-layer construction. The multi-layer construction may be in the form of a film or sheet, and may further be thermoformed or oriented, and may be produced using conventional methods and extrusion equipment known to those skilled in the art, where layers of polymer melts are combined by introducing multiple polymers. The polymer melts flow into a combining block / manifold or die, after which the melt streams are induced to flow together (still in the block / manifold or die) and exit the die together as a single stream. Alternatively, multiple polymer melt streams may be introduced into the die and combined immediately after exiting the die. outer layer
[0035] In some embodiments, one or more of the outer layers are structural layers of typically non-polar polymers or copolymers. In some embodiments, the structural layers may be coextruded adjacent to other structural layers, and the adjacent layers may be of the same or different materials. In some embodiments, the structural layers are blends of two or more polyolefins, such as, but not limited to, blends of low density polyethylene (LDPE) and linear low density polyethylene (LLDPE).
[0036] Suitable polyethylenes for the structural layer include ethylene homopolymers, copolymers of units derived from ethylene and one or more units derived from C3-C8 α-olefins or mixtures thereof. Preferably, the units derived from one or more C3-C8 α-olefin comonomers are present in an amount of up to 15% by weight based on the total weight of the ethylene-based copolymer. Ethylene homopolymers and copolymers may be produced using single-site catalysts such as Die-Glare-Natta or metallocene catalysts. Ethylene homopolymers and copolymers may be produced using gas phase, high pressure, slurry or solution processes. Ethylene homopolymers and ethylene-C3-C8 α-olefin copolymers include very low density polyethylene (VLDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE) and high density polyethylene (HDPE). VLDPE has a density of 0.860 to 0.910 g / cm as measured by ASTM D-1505 "Column Method". 3 Low density polyethylene and LLDPE have a density of 0.910 to 0.930 g / cm 3 MDPE is defined as being in the range of 0.930 to 0.945 g / cm 3 HDPE is defined as having a density of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3 The ethylene homopolymer and copolymer preferably have a melt index (MIs) of 0.01 to 400 dg / min, preferably 0.1 to 200 dg / min, more preferably 1 to 100 dg / min, as measured under conditions of 190°C / 2.16 kg according to ASTM D1238.
[0037] The preferred polypropylene for the structural layer is a propylene homopolymer, a copolymer of propylene-derived units, ethylene and C4-C 10 and one or more units derived from an α-olefin, or a mixture thereof. 4- C 10The one or more units derived from α-olefin comonomers are 35% by weight based on the total weight of the propylene copolymer. The propylene homopolymers and copolymers may be produced using single-site catalysts such as Diester-Natta or metallocene catalysts. The propylene homopolymers and copolymers may be produced using gas phase, slurry or solution processes. The propylene polymer, if a copolymer, preferably contains 2-6% by weight of ethylene-derived units as comonomer based on the total weight of the copolymer.
[0038] The structural layer may also be formed from a blend of two or more polyethylenes, two or more polypropylenes, or one or more polyethylenes and one or more polypropylenes.
[0039] In some embodiments, the preferred composition of the outer layer is the LLDPE described above, the LDPE described above, or a combination thereof. base layer
[0040] In some embodiments, the multi-layer construction comprises at least one barrier layer as a base layer. The barrier layer may comprise EVOH, nylon, such as nylon 6, nylon 6,6, nylon 12, nylon 6,12, nylon 6,66, and blends thereof, as well as co-extrusion structures of EVOH and nylon, such as EVOH / nylon and nylon / EVOH / nylon. The barrier layer further comprises polyvinylidene chloride (PVDC) and polychlorinated trifluoroethylene (PCTFE). Preferably, the barrier layer is selected from EVOH, nylon, or co-extrusion structures thereof. More preferably, the barrier layer is EVOH. bonding layer
[0041] In a preferred embodiment, the foamed tie layer in the multilayer film disclosed herein improves adhesion between a base layer (e.g., a polar polymer barrier layer) and an outer layer of a different structural layer (e.g., a polyolefin layer) compared to coextrusion of the same base layer and outer layer with a tie layer of the same material that is unfoamed. The foamed tie layer disclosed herein further provides a novel and useful combination of properties by improving one or more properties of the multilayer construction, including toughness and / or optical properties, compared to a comparable film in which the tie layer is not foamed. The improved toughness of the multilayer film with the foamed tie layer has been shown by higher dart drop impact values (ASTMD-1709). The improved optical properties of the multilayer film with the foamed tie layer have been shown by higher clarity (ASTMD-1746) and / or lower haze (ASTMD-1003).
[0042] The foamed tie layer starts with a polyolefin adhesive composition. The foaming of the tie layer is achieved by adding the polyolefin adhesive composition and a gas into an extruder and applying sufficient pressure and temperature conditions in the extruder to form a mixture of molten polyolefin adhesive composition and dissolved gas. When the mixture is discharged from the extruder through a die, the pressure of the mixture is reduced, causing the gas to come out of solution and resulting in a matrix of the molten polyolefin adhesive composition having a dispersed phase of gas cells or bubbles.
[0043] The discharge of the melt of the polyolefin adhesive composition from the extruder die also prevents the increase of heat to the composition due to a specific energy input (shaft processing or adding heat to the extruder). In many polymer foaming processes, the goal is to retain a dispersed phase of gas cells or bubbles in the final product after the polymer melt is cooled to a solid at room temperature. In contrast, the gas cells or bubbles in the foamed polyolefin adhesive composition herein partially or substantially completely collapse before curing, which allows the extrudate to be more uniform and more fully annealed when the melt of the polyolefin adhesive composition is cooled to a solid by an external cooling device at room temperature or below.
[0044] The desired collapse of the dispersed phase of gas cells is achieved by controlling the cooling rate of the extrudate to induce a higher enthalpy state in the tie layer matrix than that of the extrudate cooled at a faster rate. Without being bound by any theory, it is believed that the higher enthalpy is achieved by a more complete relaxation of the polymer chains, resulting in a higher level of crystallinity or solidification of the foamed polyolefin adhesive composition. Foaming Agent
[0045] In some embodiments, the gas addition to the extruder is accomplished by adding a chemical blowing agent to the polyolefin adhesive composition in the extruder. The chemical blowing agent may be added to the extruder by mixing with the polyolefin adhesive composition in a separate extrusion process to produce a granulated mixture of the polyolefin adhesive composition and the blowing agent. This separate extrusion process is carried out at a temperature below the thermal decomposition temperature of the blowing agent. This granulated mixture is fed to an extruder for producing a foamed bonding layer, and is subjected to pressure and temperature conditions sufficient to cause the decomposition of the blowing agent by the mixing action of the extruder screw and barrel, resulting in the generation of gas, producing a mixture of molten polyolefin adhesive composition and dissolved gas, where the gas is the gas generated by the decomposition of the blowing agent. The blowing agent can be used alone or in combination with a nucleating agent to promote a more uniform cell distribution.
[0046] Suitable chemical blowing agents include azo blowing agents, nitroso blowing agents, azide blowing agents, bicarbonate blowing agents, and combinations thereof. Examples of azo blowing agents include azodicarbamide, azodicarbamide, azodiisobutyronitrile, azodicyclohexylnitrile, azocyclohexylnitrile, azodiaminobenzene, azodicarbamide, barium azodicarboxylate, diazenedicarbonic, diazodicarbamide, diazoaminobenzene, and the like. Nitroso blowing agents include, for example, trinitrosotrimethylenetriamine, N,N'-dimethyl-N,N'-dinitroso-terephthalamide, N,N'-dinitroso-pentamethylene-tetramine, and the like. Examples of azide blowing agents include 4,4'-oxybis(benzenesulfonylhydrazide), p-toluenesulfonylhydrazide, benzenesulfonylhydrazide, toluenesulfonylhydrazide, diphenylsulfonyl-3,3'-disulfonylhydrazide, calcium azide, 4,4'-diphenyldisulfonylazide, p-toluenesulfonylazide, p-toluenesulfonylacetonehydrazone, 4,4'-oxybenzenesulfonylazide, and the like. Examples of bicarbonates include sodium bicarbonate, sodium carbonate, sodium bicarbonate, ammonium bicarbonate, ammonium carbonate, ammonium bicarbonate, ammonium nitrite, and the like. In some embodiments, nitroso blowing agents and / or azo blowing agents are preferred. The chemical blowing agents may be used alone or in combination of two or more.
[0047] In some embodiments, physical foaming is used instead of chemical foaming. In physical foaming, gas is injected directly into the polymer melt in the extruder barrel. Additional equipment is required to inject high pressure gas into the melt. In physical foaming, such as the MuCell™ process, a precise amount of gas is injected directly into the extruder barrel, regardless of the process temperature. For this reason, physical foaming is applicable at any process temperature, and the reaction temperatures of the various chemical foaming agents on the market are between 160 and 200°C.
[0048] The gases produced in chemical foaming processes or used in physical foaming processes are typically nitrogen, carbon dioxide, or mixtures thereof, however, any gas having suitable solubility in the polymer melt can be used. Nucleating Agent
[0049] When used in combination with a blowing agent, a nucleating agent is a substance, usually a small particle, that provides a nucleation site or location, in this case a bonding layer, for bubble formation within a polymer melt. Nucleating agents are used to reinforce the cell structure of foamed polymers. Some nucleating agents are "active" in that such compounds act as nucleating agents and participate in foaming by at least partially decomposing to produce gaseous components.
[0050] Examples of nucleating agents suitable for the present invention include inorganic nucleating agents and organic nucleating agents. Inorganic nucleating agents include talcum, metal oxides such as titanium dioxide and magnesium oxide, alkaline earth metal phosphates, carbonates and sulfates, clays and nanoclays, carbons and nanocarbons, pigments with suitable particle sizes, or mixtures thereof. Organic nucleating agents include polymers with a melting temperature higher than that of the polyolefin adhesive composition, terephthalic acid, mono- or polycarboxylic acids, and their salts, such as 4-tert-butylbenzoic acid, adipic acid, diphenylacetic acid, sodium succinate, sodium benzoate, or mixtures thereof, although other nucleating agents can also be used.
[0051] The amount of nucleating agent added may vary depending on the nature of the nucleating agent selected. The nucleating agent is usually present in an amount of 0.05 to 15.0% by weight based on the amount of thermoplastic polymer, more preferably 0.5 to 10.0% by weight, most preferably 0.5 to 8% by weight, and especially preferably between 2.0% and 8.0% by weight. Polyolefin-based adhesive composition
[0052] In some embodiments, the polyolefin-based adhesive composition is formed by melt blending a polyolefin with a functionalized olefin-based polymer. In one or more embodiments, the polyolefin is contacted with the functionalized olefin-based polymer prior to pelletization. In one or more other embodiments, the functionalized olefin-based polymer is contacted with the polyolefin prior to pelletization.
[0053] In other embodiments, without regard to blending the polyolefin with the functionalized olefin-based polymer, the process of combining the two components further comprises melt blending the polyolefin polymer with the functionalized olefin-based polymer in the presence of an adhesion promoting additive.
[0054] In some embodiments, the polyolefin-based adhesive composition comprises in the range of 0.5 wt% to 30 wt%, 1 wt% to 20 wt%, 2 wt% to 15 wt%, 5 wt% to 15 wt%, 6 wt% to 11 wt%, or 12 wt% to 17 wt% of the functionalized olefin-based polymer, based on the total weight of the polyolefin-based adhesive composition.
[0055] In some embodiments, the preferred composition of the polyolefin-based adhesive composition is 0.910 to 0.930 g / cm 3 and LLDPE having a density in the range of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3 and a HDPE having a density of 100 to 200 nm, wherein the HDPE is functionalized with maleic anhydride (HDPE-g-MAH). In some preferred embodiments, the HDPE-g-MAH is present in the blend of LLDPE and HDPE-g-MAH in a range of 0.5 wt.% to 30 wt.%, 1 wt.% to 20 wt.%, 2 wt.% to 15 wt.%, 5 wt.% to 15 wt.%, or 6 wt.% to 11 wt.%, based on the total weight of the polyolefin adhesive composition.
[0056] In another embodiment, the preferred composition of the polyolefin-based adhesive composition is 0.910 to 0.930 g / cm 3and LLDPE with a density in the range of 0.910 to 0.930 g / cm 3 and other LLDPEs, where the LLDPE is functionalized with maleic anhydride (LLDPE-g-MAH). In some preferred embodiments, the LLDPE-g-MAH is present in the blend of LLDPE and LLDPE-g-MAH in a range of 0.5% to 30%, 1% to 20%, 2% to 15%, 5% to 15%, or 6% to 11% by weight, based on the total weight of the polyolefin adhesive composition. Polyolefin component of polyolefin-based adhesive composition
[0057] The composition of the polyolefin component of the polyolefin adhesive composition may comprise a single ethylene-based polymer, a single propylene-based polymer, a blend of two or more ethylene-based polymers, a blend of two or more propylene-based polymers, or a blend of at least one ethylene-based polymer and at least one propylene-based polymer. Suitable ethylene-based and propylene-based polymers are described below. The one or more polyolefin composition polymers selected from ethylene-based polymers, propylene-based polymers, and combinations thereof may be the same or different from the composition polymer of the olefin-based polymer component that functionalizes the olefin-based polymer.
[0058] Suitable polyethylenes for use as the polyolefin component of the polyolefin-based adhesive include ethylene homopolymers, copolymers of units derived from ethylene and one or more units derived from C3-C8 α-olefins or mixtures thereof. Preferably, the units derived from one or more C3-C8 α-olefin comonomers are present in an amount of up to 15% by weight based on the total weight of the ethylene copolymer. Ethylene homopolymers and copolymers may be produced using a sign-glusite catalyst such as a Die-Granatta or metallocene catalyst. Ethylene homopolymers and copolymers may be produced using a gas phase process, a high pressure process, a slurry process or a solution process. Ethylene homopolymers and ethylene-C3-C8 α-olefin copolymers include very low density polyethylene (VLDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE) and high density polyethylene (HDPE). VLDPE has a density of 0.860 to 0.910 g / cm3 as measured by ASTM D-1505 "column method". 3 Low density polyethylene and LLDPE have a density of 0.910 to 0.930 g / cm 3 MDPE is in the range of 0.930 to 0.945 g / cm 3 HDPE is defined as having a density of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3 The ethylene homopolymer and copolymer preferably have a melt index (MIs) of 0.01 to 400 dg / min, preferably 0.1 to 200 dg / min, more preferably 1 to 100 dg / min, as measured under conditions of 190°C / 2.16 kg according to ASTM D1238.
[0059] Polypropylenes suitable as the polyolefin component of polyolefin-based adhesives include propylene homopolymers, propylene-derived units, and ethylene and C4-C 10 and one or more units derived from an α-olefin, or a mixture thereof. 4-C 10 One or more units derived from α-olefin comonomers are present in an amount of up to 35% by weight, based on the total weight of the propylene-based copolymer. Propylene homopolymers and copolymers may be produced using single-site catalysts, such as Ziegler-Natta catalysts or metallocene catalysts. Propylene homopolymers and copolymers may be produced using gas phase, slurry or solution processes. The propylene polymer, if a copolymer, preferably contains 2-6% by weight, based on the total weight of the copolymer, of units derived from ethylene as a comonomer.
[0060] In some embodiments, the preferred composition of the polyolefin component of the polyolefin adhesive composition is polyethylene as described above. In some embodiments, the preferred composition of the polyolefin component of the polyolefin adhesive composition is polyethylene having a density of 0.910 to 0.930 g / cm 3 It is an LLDPE in the range. Functionalized olefin-based polymer component of polyolefin-based adhesive composition
[0061] Functionalized olefin-based polymers are typically formed by grafting a functional monomer onto the backbone (i.e., the backbone) of an olefin-based polymer. The composition of the olefin-based polymer may comprise an ethylene-based polymer alone, a propylene-based polymer alone, a blend of two or more ethylene-based polymers, a blend of two or more propylene-based polymers, or a blend of one or more ethylene-based polymers and one or more propylene-based polymers. Suitable ethylene-based and propylene-based polymers are described below. The one or more polymers selected from the ethylene-based polymer, propylene-based polymer, and combinations thereof may be the same or different from the combination of polyolefin polymers.
[0062] The functional monomer may be grafted onto the olefin-based polymer by methods known to those skilled in the art. The graft may be formed, for example, by reactive extrusion. The reactive extrusion process generally involves contacting an olefin-based polymer with a functional monomer in an extruder or in a solution process to form a functionalized olefin-based polymer.
[0063] The reactive extrusion process may include any extrusion process known in the art. For example, the raw materials (e.g., olefin-based polymer and functional monomer) may be fed into a twin-screw extruder at a sufficient concentration to form a functionalized olefin-based polymer with a desired graft content. The reaction to form the functionalized olefin-based polymer may occur, for example, in a twin-screw extruder under continuous mixing and kneading. Thus, the functionalized olefin-based polymer generally comprises a linear backbone of a first olefin-based polymer with randomly distributed branches of the functional monomer, resulting in side chains that are structurally different from the backbone / main chain.
[0064] In one or more embodiments, the olefin-based polymer is contacted with the functional monomer in the presence of an initiator. The initiator can be selected from those known to those skilled in the art, such as, but not limited to, organic peroxides. However, as previously described herein, grafting can occur at high temperatures and high shear even in the absence of an initiator.
[0065] The functionalized olefin-based polymer may contain, for example, in the range of 0.001 to 100 wt %, 0.01 to 15 wt %, 0.01 to 5 wt %, or 0.1 to 3 wt % of the functional monomer based on the total weight of the functionalized olefin-based polymer.
[0066] In one or more embodiments, the functionalized polyolefin may exhibit a grafting yield ranging from, for example, 0.2% to 20%, 0.5% to 10%, or 1% to 5% by weight. The grafting yield may be determined by Fourier transform infrared spectroscopy (FTIR).
[0067] In some embodiments, the preferred composition of the functionalized olefin-based polymer is at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3 and as mentioned above, the HDPE is functionalized with maleic anhydride.
[0068] In another embodiment, the preferred composition of the functionalized olefin-based polymer is from 0.910 to 0.930 g / cm 3 and, as noted above, the LLDPE is functionalized with maleic anhydride. Functional Monomer Components of Functionalized Olefin-Based Polymers
[0069] Functional monomers include carboxylic acids and carboxylic acid derivatives, such as acrylic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, maleic anhydride, 4-methylcyclohex-4-ene-1,2-dicarboxylic acid or anhydride, bicyclo(2,2,2)oct-5-ene-2,3-dicarboxylic acid or anhydride, bicyclo(2,2,1)hept-5-ene-2,3-dicarboxylic acid or anhydride, tetrahydrophthalic acid or anhydride, methylbicyclo(2,2,1)hept-5-ene-2,3-dicarboxylic acid or anhydride, Examples of suitable functional monomers include carboxylic acids or anhydrides, x-methylnorborn-5-ene-2,3-dicarboxylic acids and anhydrides, norborn-5-ene-2,3, dicarboxylic acids and anhydrides, maleopimaric acid, 1,2,3,4,5,8,9,10-octahydronaphthalene-2,3-dicarboxylic acids and anhydrides, 2-oxa-1,3-diketospiro(4,4)non-7-ene, nadic anhydrides and anhydrides, methylnadic anhydride, himic anhydride, methylhimic anhydride and combinations thereof, and combinations thereof. Alternatively, the functional monomers may include acid and anhydride derivatives such as dialkyl maleates, dialkyl fumarates, dialkyl itaconates, dialkyl mesoconic acids, dialkyl citraconic acids, alkyl crotonates, and combinations thereof.
[0070] In some embodiments, the preferred functional monomer is maleic anhydride. Olefin-Based Polymer Component of the Functionalized Olefin-Based Polymer
[0071] The composition of the olefin-based polymer component of the functionalized olefin-based polymer may comprise a single ethylene-based polymer, a single propylene-based polymer, a blend of two or more ethylene-based polymers, a blend of two or more propylene-based polymers, or a blend of at least one ethylene-based polymer and at least one propylene-based polymer. Suitable ethylene-based and propylene-based polymers are described below.
[0072] Suitable polyethylenes as the α-olefin polymer component of the functionalized α-olefin polymer include ethylene homopolymers, copolymers of units derived from ethylene and one or more units derived from C3-C8 α-olefins or mixtures thereof. Preferably, the units derived from one or more C3-C8 α-olefin comonomers are present in an amount of up to 15% by weight, based on the total weight of the ethylene copolymer. Ethylene homopolymers and copolymers may be produced using single-site catalysts such as Die-Glare-Natta or metallocene catalysts. Ethylene homopolymers and copolymers may be produced using gas phase, high pressure, slurry or solution processes. Ethylene homopolymers and ethylene-C3-C8 α-olefin copolymers include very low density polyethylene (VLDPE), low density polyethylene (LDPE), linear low density polyethylene (LLDPE), medium density polyethylene (MDPE) and high density polyethylene (HDPE). VLDPEs are polyethylenes having a density of 0.860 to 0.910 g / cm3 as measured by ASTM D-1505 "column method". 3 Low density polyethylene and LLDPE have a density of 0.910 to 0.930 g / cm 3 MDPE is in the range of 0.930 to 0.945 g / cm 3 HDPE is defined as having a density of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3The homopolymer and copolymer of ethylene preferably have a melt index (MIs) of 0.01 to 400 dg / min, preferably 0.1 to 200 dg / min, more preferably 1 to 100 dg / min, as measured according to ASTM D1238 at 190°C / 2.16 kg.
[0073] Polypropylenes suitable as the α-olefin polymer component of the functionalized α-olefin polymer include propylene homopolymers, propylene-derived units, and ethylene and C4-C 10 and one or more units derived from an α-olefin, or a mixture thereof. 4- C 10 One or more units derived from α-olefin comonomers are present in an amount of up to 35% by weight, based on the total weight of the propylene copolymer. Propylene homopolymers and copolymers may be produced using single-site catalysts, such as Ziegler-Natta catalysts or metallocene catalysts. Propylene homopolymers and copolymers may be produced using gas phase, slurry or solution processes. The propylene polymer, if a copolymer, preferably contains 2-6% by weight, based on the total weight of the copolymer, of units derived from ethylene as monomer. Specific Embodiments
[0074] In some embodiments, the multilayer film comprises: (A) 0.910~0.930g / cm 3 LLDPE, with a density in the range of 0.910~0.930g / cm 3 or a combination thereof; and (B) one or more substrate layers comprising EVOH; (C) Each is placed between one substrate and one outer layer, and each has a density of 0.910 to 0.930 g / cm 3 and LLDPE having a density in the range of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3and a layer comprising a blend of LLDPE and HDPE having a density of from 0.5% to 30% by weight, from 1% to 20% by weight, from 2% to 15% by weight, from 5% to 15% by weight, or from 6% to 11% by weight, based on the total weight of the polyolefin adhesive composition.
[0075] In another embodiment, the multilayer film comprises: (A) 0.910~0.930g / cm 3 LLDPE, with a density in the range of 0.910~0.930g / cm 3 one or more outer or base layers comprised primarily of LDPE having a density in the range of (B) one or more substrate layers based on EVOH; (C) 0.910~0.930g / cm 3 and LLDPE having a density in the range of at least 0.945 g / cm 3 , preferably 0.945 to 0.969 g / cm 3 and one or more tie layers consisting essentially of a blend of LLDPE and HDPE-g-MAH functionalized with maleic anhydride (HDPE-g-MAH), the LLDPE and HDPE-g-MAH being present in an amount of 0.5% to 30%, 1% to 20%, 2% to 15%, 5% to 15%, or 6% to 11% by weight of the blend of LLDPE and HDPE-g-MAH, based on the total weight of the polyolefin based adhesive composition.
[0076] In another embodiment, the multilayer film comprises: (A) 0.910~0.930g / cm 3 LLDPE, with a density in the range of 0.910~0.930g / cm 3 or a combination thereof; and (B) one or more substrate layers comprising EVOH; (C) 0.910~0.930g / cm 3and LLDPE functionalized with maleic anhydride (LLDPE-g-MAH) with densities ranging from 0.910 to 0.930 g / cm 3 and a blend with another LLDPE having a density in the range of 0.5% to 30% by weight, 1% to 20% by weight, 2% to 15% by weight, 5% to 15% by weight, or 6% to 11% by weight, based on the total weight of the polyolefin adhesive composition, in the blend of LLDPE and LLDPE-g-MAH.
[0077] In another embodiment, the multilayer film comprises: (A) 0.910~0.930g / cm 3 LLDPE, with a density in the range of 0.910~0.930g / cm 3 one or more outer or base layers comprised primarily of LDPE having a density in the range of (B) one or more substrate layers based on EVOH; (C) 0.910~0.930g / cm 3 and LLDPE functionalized with maleic anhydride (LLDPE-g-MAH) with densities ranging from 0.910 to 0.930 g / cm 3 and a layer consisting essentially of a blend of LLDPE and LLDPE-g-MAH having a density in the range of 0.5% to 30% by weight, 1% to 20% by weight, 2% to 15% by weight, 5% to 15% by weight, or 6% to 11% by weight, based on the total weight of the polyolefin adhesive composition. Additives
[0078] The tie layer composition and / or other layers of the multilayer film may further include additives such as stabilizers, UV absorbers, metal deactivators, sulfur enhancers, peroxide scavengers, basic co-stabilizers, acid scavengers, nucleating agents, clarifiers, conventional fillers, dispersants, plasticizers, lubricants, emulsifiers, pigments, flow control agents, optical brighteners, flame retardants, antistatic agents, foaming agents, and mixtures thereof. In some embodiments, the tie layer composition may include 0.001 to 2 wt. % of a primary additive, based on the total weight of the tie layer composition. In some examples, the primary additive is an antioxidant. In some embodiments, the tie layer composition may include 0.001 to 2 wt. % of a secondary additive, based on the total weight of the tie layer composition. In some examples, the secondary additive is an antioxidant. In certain embodiments, the primary additive and / or secondary additive may be a processing stabilizer and / or a sterically hindered phenolic primary antioxidant. In certain embodiments, the tie layer composition may include 0.1 wt. % of a sterically hindered phenolic antioxidant, based on the total weight of the tie layer composition. The sterically hindered phenolic antioxidant may be tetrakis[methylene(3,5-di-(tert)-butyl-4-hydroxyhydrocinnamate)]methane. In certain embodiments, the tie layer composition comprises 0.1 wt. % of a hydrolytically stable phosphite processing stabilizer, based on the total weight of the tie layer composition. The hydrolytically stable phosphite processing stabilizer may be tris(2,4-ditert-butylphenyl) phosphite. Multilayer film formation
[0079] Also provided herein is a method for producing a multilayer film using an extrusion process.
[0080] In some embodiments, the multilayer constructions herein include structures produced by coextrusion of at least three polymer layers, with the middle layer being a foamed tie layer as described herein. Multilayer films having at least three polymer layers can be produced using blown film or cast film processes.
[0081] In other embodiments, the multi-layer constructions herein include structures made by co-extrusion coating at least one non-polymeric layer with two polymeric layers, where a foamed tie layer as described herein is disposed between the non-polymeric layer and the other polymeric layer. Non-polymeric substrates include, but are not limited to, metal foils and paper.
[0082] In other embodiments, the multi-layer constructions herein include structures formed by extrusion lamination of at least two non-polymeric layers, where a foamed bonding layer as described herein is disposed between the two non-polymeric layers. Non-polymeric substrates include, but are not limited to, metal foils and paper. Blown Film Process
[0083] In a preferred blown film process, at least three layers are coextruded to produce the layer configuration A / B / C, where A comprises a polar polymer, B comprises a polyolefin-based adhesive composition as a tie layer, and C comprises a non-polar polymer.
[0084] In the multilayer coextrusion blown film process, the polymers for each layer are heated in separate extruders. As the molten polymers reach the end of the barrel of each extruder, they are coextruded through a multilayer annular die. The molten polymers enter the die and air is injected through a hole in the center of the die, causing the polymer to radially expand into a capillary tube with a diameter many times the original extruded diameter. The heated film tube is then cooled and pulled upward by nip rollers, flattening the tube and trapping the air inside the tube.
[0085] The multilayer melt begins to cool as soon as it leaves the die. As the film cools, it solidifies at a height above the mold, i.e., the frost line height (FLH), forming a visible line around the polymer tube, the so-called frost line. During the production of multilayer blown films with one or more foamed bonding layers as described herein, the multilayer melt is visually observed to be opaque or very hazy as it leaves the die due to a dispersed phase of gas cells or bubbles formed in the matrix of the molten polyolefin adhesive composition. The bubbles in the dispersed phase begin to collapse immediately after formation and continue to collapse as long as the bonding layer is in a molten state. As the bubbles collapse within the bonding layer, the multilayer film becomes less opaque and therefore more transparent. Preferably, before reaching the frost line, the multilayer melt reaches substantially the same transparency as a multilayer melt of the same layers and layer composition under the same conditions but without the foamed bonding layer. The collapse of the dispersed gas phase stops at the FLH, where the melt of the multiple layers solidifies. Thus, it is desirable that the dispersed phase of gas bubbles substantially or completely collapse within the tube of multilayer melt at distances from the extruder die less than the FLH. Substantial or complete collapse of the dispersed phase of gas bubbles in the tie layer melt is indicated by visually observing that the dispersed phase of gas bubbles in the tie layer melt is not foamed prior to reaching the frost line, i.e., at distances from the mold less than the FLH, the multilayer melt becomes as transparent as possible or as close to the transparency of its multilayer analogue.
[0086] Those skilled in the art will recognize the process variables related to speed, temperature and heat transfer associated with adjusting the FLH and will be able to make the necessary changes to induce gas cell collapse in the foamed bond layer before the extruded multilayer tube reaches the frost line. Those skilled in the art will recognize that the location of the frost line in a blown film coextrusion process is a function of the heat transfer and linear speed of the blown film tube, and further understand how to adjust these principles to successfully tailor a multilayer film having a different layer arrangement and / or layer composition. In terms of direction, if the linear speed of the blown film tube is held constant or substantially constant and the heat transfer variables are adjusted, the FLH or frost line distance from the extruder die will increase by increasing the temperature of the multilayer melt, increasing the velocity of the air in the inlet tube, increasing the thickness of the film, and / or decreasing the temperature of the air in the inlet tube. In terms of direction, if the heat transfer variables are held constant or substantially constant, the FLH or frost line distance from the extruder die will increase by increasing the linear speed of the blown film tube. Generally, the FLH can be increased by increasing the take-up speed, the extruder speed, and / or the temperature of the air injected into the die to expand the tube. The take-up speed is the speed at which the polymer tube is drawn upward from the die. The extruder speed is the revolutions per minute of the extruder screw drive. Preferably, one skilled in the art will balance the adjustment of these process variables to produce a multilayer film having a foamed tie layer as described herein in a manner that maintains or achieves other desired film properties of the final multilayer film.
[0087] In a preferred embodiment, the multilayer film may be formed by coextrusion of multiple melts of thermoplastic polymers, the layers including at least one barrier layer, at least one structural layer, and at least one tie layer between the barrier layer and the structural layer.
[0088] To form a multilayer film, the polyolefin adhesive composition and the gas are added to an extruder and mixed under conditions of pressure and temperature sufficient to produce a mixture of molten polyolefin adhesive composition and dissolved gas. Meanwhile, in a separate extruder, a portion of the first polymer and the second polymer are heated to a temperature sufficient to allow extrusion. The polyolefin adhesive, the first polymer and the second polymer are then co-extruded to form a multilayer melt. The temperature of the multilayer melt is then reduced at a controlled rate to induce at least a portion of the gas cells to collapse.
[0089] Preferably, the first polymer is a polar polymer and the second polymer is a non-polar polymer. The polar polymer is preferably EVOH or nylon. The non-polar polymer is preferably an ethylene-based polymer alone, a propylene-based polymer alone, a blend of two or more ethylene-based polymers, a blend of two or more propylene-based polymers, or a blend of one or more ethylene-based polymers and one or more propylene-based polymers.
[0090] In some embodiments, the gas that is dissolved in the bonding layer can be generated within the extruder by pyrolysis of a chemical blowing agent, such as an azo blowing agent, a nitroso blowing agent, an azide blowing agent, a bicarbonate blowing agent, or a combination thereof, hi other embodiments, the gas is added to the extruder from an external source. Cast Film Process
[0091] In a preferred cast film process coextrusion process, at least three polymer layers are coextruded to produce a layer configuration A / B / C, where A comprises a polar polymer, B comprises a polyolefin adhesive composition as a tie layer, and C comprises a non-polar polymer.
[0092] In the multilayer coextrusion cast film process, the polymers for each layer are heated in separate extruders. When the molten polymers reach the end of the barrel of each extruder, they are coextruded through a multilayer flat die system into the final shape. Upon exiting the die, the multilayer melt enters a cooling unit where water-cooled chill rolls reduce the temperature and solidify the film.
[0093] During the production of multilayer cast films having one or more foamed bonding layers, the multilayer melt is visually observed to be opaque or very hazy as it leaves the die due to a dispersed phase of gas cells or bubbles formed in the matrix of the molten polyolefin based adhesive composition.
[0094] As noted above, for blown films, it is desirable to maximize the visual clarity of the multilayer melt prior to solidification. Those skilled in the art will recognize that useful modifications to conventional cast film equipment, such as melt temperature, film production rate, extruder speed, and / or other operating conditions, such as die to cold roll distance, cold roll temperature, etc., will result in the desired maximum collapse of dispersed gas bubbles within the foamed bonding layer. Co-extrusion coating
[0095] A preferred coextrusion coating process combines at least two polymer layers with one non-polymeric substrate to produce a layer configuration A / B / C, where A comprises a polar polymer, a non-polar polymer, or a combination thereof, B comprises a polyolefin-based adhesive composition as a tie layer, and C comprises the non-polymeric substrate.
[0096] In a co-extrusion coating process, an extruder forces molten thermoplastic resin through a flat die onto a moving substrate. The resulting product is a permanently coated substrate.
[0097] As noted above, for blown films, it is desirable to maximize the visual clarity of the multilayer melt prior to solidification. Those skilled in the art will recognize useful modifications to operating conditions such as film production rate and extruder speed, and / or conventional coextrusion coating equipment, such as the die-to-substrate distance, the substrate temperature, and / or equipment to limit multilayer melt cooling between the die and substrate that maximizes the chance of collapse of the gas bubbles dispersed in the foamed bond layer. Extrusion Lamination
[0098] A preferred extrusion lamination process combines at least one polymeric layer with two non-polymeric substrates to produce a layer configuration A / B / C, where A comprises the non-polymeric substrate, B comprises the polyolefin-based adhesive composition as a tie layer, and C comprises the non-polymeric substrate (e.g., foil / tie layer / paper).
[0099] In the extrusion lamination process, an extruder forces molten thermoplastic resin into a flat die, which acts as an adhesive layer between the substrates, resulting in a product in which the layers of substrates are permanently bonded together.
[0100] As noted above, for blown films, it is desirable to maximize the visual clarity of the multilayer melt prior to solidification. Those skilled in the art will recognize useful modifications to conventional extrusion lamination equipment, such as operating conditions such as melt temperature, film production rate, extruder speed, and / or means to limit the distance from the die to the substrate, the temperature of the substrate, and / or cooling of the multilayer melt between the die and the substrate that results in the desired maximum collapse of the gas bubbles dispersed in the foamed bond layer.
[0101] The following examples are illustrative of the present invention. However, those skilled in the art will recognize many variations within the spirit of the present invention and the scope of the claims. In order to facilitate a better understanding of the present invention, the following are examples of preferred embodiments. The following embodiments should not be construed as limiting or defining the scope of the present invention. Working Example
[0102] The following examples are included to illustrate preferred embodiments of the present invention. Those skilled in the art will appreciate that the techniques disclosed in the following embodiments represent techniques that the inventors have discovered to work well in embodiments of the present invention and can be considered to constitute preferred forms of embodiments of the present invention. However, those skilled in the art will appreciate, in light of this disclosure, that many changes can be made in the specific embodiments disclosed and still obtain the same or similar results without departing from the spirit and scope of the present invention.
[0103] The following examples provide compositions useful as tie layer adhesive compositions. Exemplary tie layer adhesive compositions can be used to bond polar polymer layers, such as EVOH, to other polymer layers in multilayer constructions. The polyolefin-based adhesive compositions disclosed herein are particularly suitable for bonding structural layers (e.g., copolymers and / or blends of ethylene-based and / or propylene-based homopolymers with non-polar comonomers) to oxygen barrier layers (e.g., EVOH or nylon) or combinations thereof in coextruded barrier constructions. The foamed adhesive layer compositions of the present invention are studied by controlling the temperature of the adhesive layer polymer composition in the extruder, during and after extrusion.
[0104] The raw materials used here are shown in Table 1. [Table 1]
[0105] The tie layer materials used herein are shown in Table 2. The components are listed as weight percent based on the total weight of the tie layer polymer. Tie layer compositions TLP1, TLP2 and TLP4 are prepared by mixing the formulations in an 18 mm Leistritz twin screw extruder at a temperature below 190° C., a speed of 15 lb / hr and 700 rpm. [Table 2] Test Method
[0106] Dart Drop (g): Measured in accordance with ASTM D1709-04(2016) using a dart drop height of 26 inches (F50).
[0107] Haze (%): Film haze measurements were performed according to ASTM D1003.
[0108] The crystallinity, heat of fusion and crystallization temperature were measured by differential scanning calorimetry according to ASTM D3418-03.
[0109] Narrow angle scattering: Film NAS was measured according to ASTM D1746(2015).
[0110] Density was determined according to ASTM D1505.
[0111] The MI / MFR was determined based on D1238 (conditions 190°C / 2.16g). General example
[0112] The interface between the tie layer and the EVOH layer can limit the impact strength in multilayer films. In this invention, a new technique for producing blown multilayer films with foamed tie layers demonstrates improved performance of multilayer constructions with different layers bonded together. The tie layer resin is compounded with a chemical blowing agent at a temperature below its decomposition temperature. The multilayer polymer coextrusion herein essentially consists of a multiple single screw extruder system with a coextrusion feedblock, a series of layer multiplication elements, and an exit die. In the feedblock, the melt streams merge into parallel layers.
[0113] Coextrusion of 3 mil blown films was performed using a Dr. Collin™ blown film line. The line consisted of seven 25:1 L / D single screw extruders A / B / C / D / E / F / G with grooved feed zones. EVOH was fed into extruder D as the base layer. The comparison tie layer polymer and the inventive tie layer polymer were fed simultaneously into extruders C and E. The same materials were fed simultaneously into the outer layer extruders A, B, F, and G to produce a 5-layer film with OL as the outer layer, TL as the tie layer, and BL as the base layer: OL / TL / BL / TL / OL. The relative thicknesses of each layer were 37 / 7 / 12 / 7 / 37 or 40 / 4 / 12 / 4 / 40, with each number representing the percentage of the total multilayer thickness of each layer. The screw diameters (mm) of each extruder were 25 / 25 / 20 / 20 / 20 / 25 / 25. The annular die had a diameter of 60 mm and used a dual lip air ring cooling system. The die lip gap was set at 2 mm and the blow-up ratio (BUR) was 2.5. The lay flat was approximately 23-24 cm. The frost line height was set at 5.5 in.
[0114] In all the following examples, OL Comp. is the composition of the outer layer, BL Comp. is the composition of the base layer, and TL Comp. is the combination of the two tie layers for each example. TL Cylinder.1, TL Cylinder.2, and TL Cylinder.3 Temperatures are the approximate average temperatures of the adhesive layer material in the 1 / 13, 2 / 3, and final 1 / 3 of the extruder barrel length measured for each example. TL Adapter and TL Die Temperatures are the approximate average temperatures of the tie layer material in the adapter and in the die block between the extruder barrels measured for each example. Examples 1 to 12
[0115] The test conditions and film performance results for Examples 1 to 12 are shown in Table 3. Examples 1 to 12 all have a layer thickness configuration of 37 / 7 / 12 / 7 / 37. The outer layers and base layer are common to all embodiments to demonstrate the performance difference of multilayer films with different tie layer compositions.
[0116] Examples 1, 2, 7 and 8 all have a common low temperature profile for the extruder. Examples 3, 4, 9 and 10 all have a common medium temperature profile for the extruder. Examples 5, 6, 11 and 12 all have a common high temperature profile for the extruder.
[0117] Examples 1, 3 and 5 use a tie layer of a commercial olefinic adhesive composition containing no blowing agent, while Examples 2, 4 and 6 use the same composition prepared in a manufacturing lab, Examples 7, 9 and 11 use a tie layer of a composition containing 1000 ppm of a blowing agent, while Examples 8, 10 and 12 use the same composition containing 2000 ppm of the same blowing agent. Dart Drop
[0118] In the examples performed with the lower extruder temperature profile, Examples 7 and 8, which used a foamed tie layer, demonstrated a dart drop result of 258 g, while Comparative Examples 1 and 2 achieved dart drop results of 174 g and 162 g, respectively. This represented a 48% improvement when comparing the low values of the two films with foamed tie layers to the high performance of the two Comparative Examples.
[0119] In the examples performed with the mid-range extruder temperature profile, Examples 9 and 10, which used a foamed tie layer, demonstrated dart drop results of 300 g and 255 g, respectively, while Comparative Examples 3 and 4 achieved dart drop results of 198 g and 159 g, respectively. This represented a 29% improvement when comparing the low values of the two films with foamed tie layers to the high performance of the two Comparative Examples.
[0120] In the examples run with the higher extruder temperature profiles, Examples 11 and 12, which used a foamed tie layer, showed dart drop results of 327 g and 309 g, respectively, and Comparative Examples 5 and 6 showed dart drop results of 219 g and 171 g, respectively, representing a 41% improvement over the lower values of the two films with foamed tie layers and the high performance of the two Comparative Examples.
[0121] All examples using the foamable tie layer showed improved dart drop performance across all three extruder temperature profiles compared to all examples using the conventional tie layer. transparency
[0122] In the examples performed with the lower extruder temperature profile, Examples 7 and 8 using a foamed tie layer had transparency results of 34.2% and 40.7%, respectively, and Comparative Examples 1 and 2 had transparency results of 25% and 33.7%, respectively, showing that Example 7 was 37% better than Example 1 and 1% better than Example 2, and Example 8 was 21% better than Example 1 and 63% better than Example 2.
[0123] In the examples performed with the mid-range extruder temperature profile, Examples 9 and 10, which used a foamed tie layer, showed clarity results of 53.9% and 40.7%, respectively, and Comparative Examples 3 and 4 showed clarity results of 26.8% and 23.8%, respectively, which represents a 52% improvement over the poor values of the two films with foamed tie layers and the high performance of the two Comparative Examples.
[0124] In the examples performed with the higher extruder temperature profile, Examples 11 and 12, which used a foamed tie layer, showed clarity results of 60.5% and 55.1%, respectively, and Comparative Examples 5 and 6 showed clarity results of 48.2% and 26.7%, respectively, representing a 14% improvement over the lower values of the two films with foamed tie layers and the higher performance of the two Comparative Examples.
[0125] In the examples using the lower extruder temperature profile, the clarity of the film was improved or at least maintained, and in all examples using the mid-range and high extruder temperature profiles, the clarity results showed that the clarity of all examples using a foamed tie layer was improved. Hayes
[0126] In the examples performed with the low extruder temperature profile, Examples 7 and 8 using a foamed tie layer had haze results of 11.68% and 12.52%, respectively, and Comparative Examples 1 and 2 had haze results of 12.53% and 12.98%, respectively, indicating that Example 7 had reduced haze compared to Examples 1 and 2, and Example 8 had reduced or matched haze compared to Examples 1 and 2.
[0127] In the examples using the mid-range extruder temperature profile, Examples 9 and 10 using a foamed tie layer showed haze results of 13.05% and 12.83%, respectively, and Comparative Examples 3 and 4 showed haze results of 14.55% and 14.32%, respectively. Both Example 9 and Example 10 showed about a 10% reduction in haze values compared to the two Comparative Examples.
[0128] In the examples performed with the higher extruder temperature profile, Examples 11 and 12, which used a foamed tie layer, showed haze results of 13.8% and 13.47%, respectively, and Comparative Examples 5 and 6 showed haze results of 15.73% and 15%, respectively. Both Example 11 and Example 12 showed a reduction in haze values of 10% or more compared to the two Comparative Examples.
[0129] The multilayer film examples with foamed tie layers using the lower extruder temperature profile exhibited reduced or equivalent haze, while the multilayer films using both the mid-range and higher extruder temperature profiles exhibited reduced haze. Differential Scanning Calorimetry
[0130] DSC1 st Peak and DSC2 nd The peaks represent the melting temperatures of the components in the outer layer composition. rdThe peak represents the melting temperature of the base layer composition. The high DSC ΔH values of the examples with foamed tie layers indicate a high enthalpy state of the multilayer film. Due to the only change in these examples versus the comparative examples, this high enthalpy indicates more cure or crystallinity in the foamed tie layer, consistent with the collapse of gas cells before the tie layer cures. [Table 3] Examples 13 to 16
[0131] The test conditions and film performance results for Examples 13-16 are shown in Table 4. All of Examples 13-16 have a layer thickness configuration of 40 / 4 / 12 / 4 / 40. The outer layers and base layer are common to all embodiments to demonstrate the performance difference of multilayer films with different tie layer compositions.
[0132] Examples 13, 14, 15 and 16 have a common high temperature profile in both extruders.
[0133] Example 13 uses a tie layer of a commercial olefin-based adhesive composition containing no blowing agent, Example 14 uses the same composition prepared in the laboratory, and Examples 15 and 16 use tie layers of the same composition containing 1000 ppm and 2000 ppm of the same blowing agent, respectively. Dart Drop
[0134] In the examples performed with the higher extruder temperature profiles, Examples 15 and 16, which utilized a foamed tie layer, demonstrated dart drop results of 303 g and 312 g, respectively, while Comparative Examples 13 and 14 achieved dart drop results of 213 g and 177 g, respectively, representing an improvement from 42% when comparing the lower values of the two films with foamed tie layers to the higher performance of the two Comparative Examples.
[0135] The two examples with the foamed bonding layer had improved dart drop performance compared to the two examples with the conventional bonding layer. transparency
[0136] In the examples performed with the lower extruder temperature profiles, Examples 15 and 16 using a foamed tie layer had clarity results of 58.8% and 55.9%, respectively, and Comparative Examples 13 and 14 had clarity results of 43.5% and 31.87%, respectively, representing a 29% improvement over the lower values of the two films with foamed tie layers and the higher performance of the two Comparative Examples.
[0137] The clarity of the two embodiments using the foamed tie layer was improved compared to the two examples having the conventional tie layer. Hayes
[0138] In the examples performed with the lower extruder temperature profile, Examples 15 and 16, which used a foamed tie layer, had haze results of 14.18% and 14.6%, respectively, and Comparative Examples 13 and 14 had clarity results of 15.6% and 15.87%, respectively, representing a 6% reduction in measured haze values when comparing the higher values of the two films with foamed tie layers to the lower haze values of the two comparative examples.
[0139] The two examples using the foamed tie layer showed improved haze performance compared to the two examples having the conventional tie layer. Differential Scanning Calorimetry
[0140] DSC1 st Peak and DSC2 nd The peaks indicate the melting temperatures of the components in the outer layer composition. rd The peak indicates the melting temperature of the base layer composition. The high DSC ΔH values of the examples with foamed tie layers indicate a high enthalpy state of the multilayer film. Due to the only change in these examples versus the comparative examples, this high enthalpy indicates more cure or crystallinity in the foamed tie layer, consistent with the collapse of gas cells before the tie layer cures. [Table 4] Examples 17 to 19
[0141] The test conditions and film performance results for Examples 17-19 are shown in Table 5. Examples 17-19 all have a layer thickness configuration of 40 / 4 / 12 / 4 / 40. The outer layer, base layer and tie layer are common to all embodiments to demonstrate the effect of the temperature of the tie layer containing the blowing agent at the extruder die on the performance of the multilayer film produced. For Examples 17, 18 and 19, the temperatures measured at the extruder die are 190°C, 221°C and 230°C, respectively.
[0142] Example 17 is a comparative example because the temperature of the tie layer is not sufficient to activate significant foaming of the tie layer (if any). Examples 18 and 19, which have sufficient tie layer temperatures to foam the tie layer, show improved dart drop, higher clarity, and reduced haze compared to Comparative Example 17. [Table 5]
[0143] Although the present invention and its advantages have been described in detail, it should be understood that various changes, substitutions and modifications can be made herein without departing from the spirit and scope of the present invention as defined by the appended claims. Moreover, the scope of the present specification is not intended to be limited to the specific embodiments of the processes, machines, film structures, layer compositions, apparatus, methods, and / or steps described herein. As one skilled in the art can readily appreciate from the present disclosure, any currently existing or hereafter developed processes, machines, film structures, layer compositions, means, methods, and / or steps that function substantially the same as the corresponding embodiments described herein or achieve substantially the same results can be utilized in accordance with the present invention. Thus, the claims are intended to include these processes, machines, film structures, layer compositions, apparatus, methods, and / or steps.
Claims
1. A film, a. a base layer; b. a first outer layer; c. a first bonding layer disposed between the first outer layer and the base layer, the first bonding layer comprising a first foamed polyolefin-based adhesive composition; the first foamed polyolefin-based adhesive composition comprises LLDPE and HDPE-g-MAH, the HDPE-g-MAH being functionalized with maleic anhydride; and A film, wherein the first foamed polyolefin-based adhesive composition comprises a dispersed phase of gas cells, at least a portion of the gas cells being at least partially collapsed.
2. The first foamed polyolefin adhesive composition is a. adding a polyolefin adhesive composition and a gas to an extruder; b. mixing the polyolefin adhesive composition and the gas in the extruder under conditions of pressure and temperature sufficient to form a mixture of the molten polyolefin adhesive composition and the dissolved gas; c) reducing the pressure of the mixture by an amount sufficient to expel the mixture through a die attached to the extruder to produce a matrix of molten polyolefin based adhesive composition containing a dispersed phase of gas cells; d) The film of claim 1, comprising the product of a reaction that reduces the temperature of the matrix of the molten polyolefin adhesive composition containing the dispersed phase of the gas cells at a rate that induces at least a partial collapse of the gas cells before the polyolefin adhesive composition solidifies.
3. 3. The film of claim 2, wherein the gas is generated in the extruder by thermal decomposition of a chemical blowing agent.
4. 4. The film of claim 3, wherein the chemical blowing agent comprises an azo blowing agent, a nitroso blowing agent, an azide blowing agent, a bicarbonate blowing agent, or a combination thereof.
5. The film of claim 2 , wherein the gas is added to the extruder from an external source.
6. The film of claim 2 , wherein the gas is nitrogen, carbon dioxide, or a mixture thereof.
7. The polyolefin adhesive composition comprises: a. the LLDPE; b. A reaction product of said mixture with HDPE-g-MAH, 3. The film of claim 2, wherein the mixture is heated to a temperature sufficient to melt at least a portion of the LLDPE and at least a portion of the HDPE-g-MAH, thereby melting and blending the mixture.
8. The HDPE-g-MAH is a. HDPE; b. the reaction product of a mixture with maleic anhydride; 8. The film of claim 7, wherein the maleic anhydride is grafted to the HDPE by a reactive extrusion process or a solution process.
9. The film of claim 8, wherein the HDPE-g-MAH is present in the range of 0.5% to 30% by weight based on the total weight of the polyolefin adhesive composition.
10. The film of claim 9, wherein the maleic anhydride is present in an amount ranging from 0.2% by weight to 20% by weight based on the total weight of the HDPE-g-MAH.
11. The film of claim 7, wherein the LLDPE has a density of 0.910 to 0.930 g / cm 3 .
12. The first outer layer is a polyethylene homopolymer, a copolymer or units derived from ethylene, and one or more ethylenically unsaturated C 3 -C 8 Units derived from non-polar comonomers, polypropylene homopolymers, copolymers or units derived from propylene, and ethylene and ethylenically unsaturated C 4 -C 10 The film of claim 1 comprising units derived from one or more non-polar comonomers, or a combination thereof.
13. The film of claim 1 , wherein the base layer comprises an ethylene-vinyl-alcohol copolymer, a polyamide, or a combination thereof.
14. a. a second outer layer; 2. The film of claim 1, further comprising: a second tie layer disposed between said second outer layer and said base layer, said second tie layer comprising a second foamed polyolefin based adhesive composition.
15. The first foamed polyolefin adhesive composition is a. adding a polyolefin adhesive composition and a gas to an extruder; b. mixing the polyolefin adhesive composition and the gas in the extruder under conditions of pressure and temperature sufficient to form a mixture of the molten polyolefin adhesive composition and the dissolved gas; c. reducing the pressure of the mixture by an amount sufficient to expel the mixture and the dissolved gas through a die attached to the extruder to produce a matrix of the molten polyolefin based adhesive composition containing gas cells; d) The film according to claim 14, comprising a reaction product that reduces the temperature of the matrix of the molten polyolefin adhesive composition containing the gas cells at a controlled rate before the polyolefin adhesive composition solidifies, thereby inducing at least a portion of the gas cells to collapse.